Negative affect and chemical intolerance as risk factors for building-related symptoms: a controlled exposure study - Fiedler, Nancy; Kelly-McNeil, Kathie; Ohman-Strickland, Pamela; Zhang, Junfeng; Ottenweller, John; Kipen, Howard M (Psychosomatic medicine, 2008)
To assess whether differences in negative affect (NA) and chemical intolerance (CI) affect responses to chemical mixtures and stress in a controlled experimental model. Participants were 130 nonsmoking, healthy women, recruited from a university community. Participants completed the Positive and Negative Affect Scale and the Chemical Odor Intolerance Index. In separate sessions 1 week apart, they were exposed to volatile organic compounds (VOCs), VOCs with ozone (VOCs+O3), and ambient or filtered air with a 1-minute spike of VOCs (masked clean air). During each session, half of the participants performed a videotaped speech stressor and half performed simple arithmetic. Before, during, and after each session, salivary cortisol samples were collected, and subjects completed neurobehavioral tests and used a ratio scale to rate physical, cognitive, and anxiety symptoms. Relative to low NA or low CI, neither the high NA nor the high CI groups reported significantly more symptoms in response to any exposure condition. High NA subjects reported more anxiety symptoms in response to the speech stressor but did not have higher cortisol than low NA subjects. High NA subjects, however, were more distressed by the experimental conditions than were low NA subjects. Low NA subjects reported more severe anxiety in the VOCs+O3 with psychological stress condition. Subjects high in NA were more anxious after a stressor but were not more physically symptomatic in response to increasing chemical exposures. A disposition toward high or low CI did not result in a differential symptomatic response to controlled chemical exposures.